Macro-Cycles of Global Economic Growth: The Dynamics of State and Market Driven Strategies of Development - Fallas Santana, Agustín (Universidad de Costa Rica, 2018)
This paper proposes a political economy analytical framework to study the standard periodization of capitalist development established by economic history, as long cycles of policy deployment, in which the market and the state alternate as the leading forces driving world economic growth. For this purpose, the paper dwells on the economic and political history of capitalist development to support the thesis that major global economic crises trigger shifts in the development paradigm. In addition, the proposed analytical framework is compared with existing theories and explanations on capitalist cycles and economic crises.